Alternative Medicine Methods Used for Weight Loss and Diabetes Control by Overweight and Obese Hispanic Immigrant Women. (June 2020) - Lindberg, Nangel M.; Vega-López, Sonia; Arias-Gastelum, Mayra; Stevens, Victor J.
Introduction: Middle-aged Hispanic women have the highest prevalence of overweight and lifetime risk for diabetes of all gender/racial groups. This study examines use of alternative medicine for weight loss and diabetes management among overweight and obese Mexican American women with or at risk for diabetes. Method: As part of a diabetes risk-reduction intervention targeting overweight and obese Hispanic women at a federally qualified health center in Hillsboro, Oregon, we administered a survey of different treatment modalities, including alternative medicine, traditional Mexican medicine, and home remedies to 85 Hispanic women. We also asked participants how often they disclosed their use of alternative methods to their providers. Results: Nearly all participants with diabetes (97%) reported using at least one alternative strategy for diabetes control, with home remedies, commercial weight-loss products, and herbal teas being the most endorsed. Most participants with diabetes and half of those without diabetes reported never telling their provider. Conclusion: This group of women reported a high prevalence of use of alternative methods for weight control and diabetes management. Yet most participants with diabetes never reported this use to a health care provider. To ensure patient safety, providers treating Hispanic women need to probe for complementary and alternative medicine practices.